1996
DOI: 10.1016/s0886-3350(96)80040-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a diffractive bifocal and a monofocal intraocular lens

Abstract: The diffractive bifocal IOL performed well at distance and near. Patients who no longer require spectacles will benefit significantly from a bifocal IOL, but many with a bifocal IOL in one eye will require spectacles for the fellow eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
2
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 13 publications
0
35
2
6
Order By: Relevance
“…If intermediate vision was assessed at distances greater than 70 cm, a statistically significant difference in visual acuity favouring the monofocal group (SN60AT; SN60AT) would probably be found. There was no disagreement between our results and the literature on near and intermediate visual acuity favouring multifocal lenses over monofocal lenses (22,(28)(29)(30) . Hutz et al (28) reported similar data on the superiority of Tecnis™ MF lenses for intermediate vision compared with Restor™ and other monofocal lenses.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…If intermediate vision was assessed at distances greater than 70 cm, a statistically significant difference in visual acuity favouring the monofocal group (SN60AT; SN60AT) would probably be found. There was no disagreement between our results and the literature on near and intermediate visual acuity favouring multifocal lenses over monofocal lenses (22,(28)(29)(30) . Hutz et al (28) reported similar data on the superiority of Tecnis™ MF lenses for intermediate vision compared with Restor™ and other monofocal lenses.…”
Section: Discussioncontrasting
confidence: 64%
“…If intermediate vision was assessed at distances greater than 70 cm, a statistically significant difference in visual acuity favouring the monofocal group (SN60AT; SN60AT) would probably be found. There was no disagreement between our results and the literature on near and intermediate visual acuity favouring multifocal lenses over monofocal lenses (22,(28)(29)(30) . Hutz et al (28) Hida WT, Nakano CT, Yamane I, Motta AFP, Tzeliks PF, Guimaraes AS, Alencar LM, Ventura DSF, Alves MR, Kara José Júnior N Leyland et al (22) did a meta-analysis of studies comparing multifocal and monofocal lenses and reported a better uncorrected far visual acuity in patients with monofocal lenses, while other studies found no difference (29,30) .…”
Section: Sn60at/sn60wf (N=32) Restor (N=16) Tecnis Mf (N=23) Independcontrasting
confidence: 64%
See 1 more Smart Citation
“…Multifocal IOLs based on either diffractive optics or zones of varying refractive power, divide incoming light into two or more focal points and allow up to 50 per cent of patients to attain spectacle independence, 41 however, due to their design, multifocal implants are frequently associated with poorer contrast sensitivity than monofocal IOLs [42][43][44] and an increased incidence of troublesome visual phenomena including glare and halos. 45,46 To avoid such disturbing visual effects and restore natural accommodative function, the ultimate goal in ongoing AIOL and presbyopia research is to refill the capsular bag with a substance able to mimic the behaviour of the youthful lens mass. 5,47,48 To date, elastic polymers 48,49 and fluid filled balloons 50 have been trialled in animal eyes but not yet in humans in vivo.…”
mentioning
confidence: 99%
“…13 Diffractive IOLs are less pupil-dependent and have advantages over refractive IOLs in near vision, 14 however, they can induce slight disturbances of night-vision and a reduction in contrast sensitivity. [15][16][17] New optical designs applied to pseudoaccommodating IOLs combine refractive and diffractive optics to reduce the disadvantages of conventional IOLs with either refractive or diffractive designs. 5,18 The present review will focus on the visual and optical performance of hybrid IOLs.…”
mentioning
confidence: 99%